Análisis de los factores que determinan la sostenibilidad y sustentabilidad de la economía social y solidaria para el cultivo y la comercialización de productos hortofrutícolas en los cantones Mejía y Rumiñahui. - Arias Sañay, Johanna Vanessa (2013)
The analysis of the factors that determine the sustainability and sustainability of social economy for the cultivation and marketing of horticultural products in the cantons Mejia and is primarily Rumiñahui investigate how social economy and resolve the effect produced within the economic aspect of wealth creation horticultural products as it relates the social and solidarity to take into account the consequences of economic activity in society in general. Therefore, the Social Solidarity Economy lays the foundation of the cooperative philosophy and reality welcomes the following entities: Cooperative Societies, Mutual Societies and Social Security, savings banks, Agricultural Transformation Societies, etc.